2021
DOI: 10.1155/2021/9572235
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus and Associated Factors among Pregnant Women Attending Antenatal Care Services at Public Health Facilities in Nekemte Town

Abstract: Background. Viral hepatitis is an emerging global health problem. A pregnant mother infected with the hepatitis B virus has a high rate of vertical transmission, causing adverse fetal and neonatal outcomes. Understanding the magnitude of the problem and associated factors has paramount importance to avert such adverse fetal and neonatal outcomes. Therefore, the main aim of this study was to assess the seroprevalence of hepatitis B virus and associated factors among pregnant women attending antenatal care clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
3
0
0
Order By: Relevance
“…The risk factor that associated with the hepatitis b among pregnant women in kupang city was having >1 sexual partners, this finding is in agreement with study conducted among pregnant women in DKI Jakarta that found that having >1 sexual partner is the risk factor of hepatitis B and pregnant women who have >1 sexual partner (Eba et al, 2021;Umare et al, 2016). As one of sexual transmitted disease during sexual contact Hepatitis B Virus will migrate which increases with the duration of sexual activity and the number of sexual partners (Tesfu et al, 2023), moreover when it is unprotected and is done with multiple partners, the transmission rate will be increased (Alemu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The risk factor that associated with the hepatitis b among pregnant women in kupang city was having >1 sexual partners, this finding is in agreement with study conducted among pregnant women in DKI Jakarta that found that having >1 sexual partner is the risk factor of hepatitis B and pregnant women who have >1 sexual partner (Eba et al, 2021;Umare et al, 2016). As one of sexual transmitted disease during sexual contact Hepatitis B Virus will migrate which increases with the duration of sexual activity and the number of sexual partners (Tesfu et al, 2023), moreover when it is unprotected and is done with multiple partners, the transmission rate will be increased (Alemu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the overall prevalence of HBV infection among pregnant women attending ANC services in the study area was 5.7% with (95% CI, 3.74-8.61). The prevalence of HBV infection was nearly similar to results reported in Shone, Nekemte, Bishoftu, and Felegehiwot referral hospitals 4.9%, 27 5.8%, 28 6.5%, 18 and 4.7% 29 , respectively.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the overall prevalence of HBV infection among pregnant women attending ANC services in the study area was 5.7% with (95% CI, 3.74-8.61). The prevalence of HBV infection was nearly similar to results reported in Shone, Nekemte, Bishoftu, and Felegehiwot referral hospitals 4.9%, 27 5.8%, 28 6.5%, 18 and 4.7% 29 , respectively. The result of this study was relatively high when compared to the result reported from Addis Ababa at 3.7%, 20 7.8% Southern Ethiopia, 30 Gandhi memorial hospital at 2.3%, 31 Agena health center in the Gurage zone at 4.1%, 32 Uganda at 2.1% 33 , and Rwanda 3.1%.…”
Section: Discussionsupporting
confidence: 85%